2019
DOI: 10.1056/nejmoa1716734
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Perfusion or Fractional Flow Reserve in Coronary Disease

Abstract: BACKGROUNDIn patients with stable angina, two strategies are often used to guide revascularization: one involves myocardial-perfusion cardiovascular magnetic resonance imaging (MRI), and the other involves invasive angiography and measurement of fractional flow reserve (FFR). Whether a cardiovascular MRI-based strategy is noninferior to an FFRbased strategy with respect to major adverse cardiac events has not been established. METHODSWe performed an unblinded, multicenter, clinical-effectiveness trial by rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
238
1
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 363 publications
(262 citation statements)
references
References 22 publications
5
238
1
18
Order By: Relevance
“…Previous work from Cook et al correlated high coronary flow reserve values to cases with positive FFR but negative instantaneous flow ratio (iFR), questioning wether the low FFR values reflect flow-limiting stenosis [20]. The recent MR-INFORM study showed that a CMR-guided revascularization strategy led to less revascularization while being non-inferior to an FFR-guided strategy by a composite endpoint of death, myocardial infarction and target vessel revascularization [21]. The overall low classification agreement between QFR and FFR with MPS and CMR may thus reflect the cumbersome progress of identifying myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from Cook et al correlated high coronary flow reserve values to cases with positive FFR but negative instantaneous flow ratio (iFR), questioning wether the low FFR values reflect flow-limiting stenosis [20]. The recent MR-INFORM study showed that a CMR-guided revascularization strategy led to less revascularization while being non-inferior to an FFR-guided strategy by a composite endpoint of death, myocardial infarction and target vessel revascularization [21]. The overall low classification agreement between QFR and FFR with MPS and CMR may thus reflect the cumbersome progress of identifying myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Three other works were suggestive of a significant BACO in which the RR of the composite outcome was towards nullity compared to the RR of mortality. 29,30,35 These works Regarding the positive controls, the CAPRICORN study showed that carvedilol, compared with placebo, was not significantly associated with the composite outcome (RR = 0.94; 95% CI: 0.84 to 1.06) but was associated with a 22% reduction in mortality (BACO index: 0.24; 95% CI: -0.15 to 0.64). On the other hand, in the EXPEDITION study, the use of cariporide was associated with an 18% lower incidence of the composite outcome, but with a 53% higher mortality, compared with placebo (BACO index: -0.48; 95% CI: -1.03 to 0.08).…”
Section: Resultsmentioning
confidence: 99%
“…In a more current study (MR-INFORM), it was shown that decisions in the diagnostic pathway in patients with a higher risk of a cardiovascular event can be guided as safely by cardiac magnetic resonance imaging (CMR) as they are by invasive FFR. Regarding the ISCHEMIA trial as well as the MR-INFORM study, always in light of the specific patient collective, it is clear that patients should be selected precisely to be referred to ICA [15,16,30]. This requires the integration of patient information by generating risk-stratification scores estimating the presence of obstructive CAD as well as non-invasive new imaging technics using self-improving machine learning software.…”
Section: Discussionmentioning
confidence: 99%